Complete transection of the bilateral main bronchus in a 5-year-old patient: a case report - Weimin Wang; Yanliang Yang; Siming Bi; Xiaozheng Lv; Huihui Xu (Journal of Cardiothoracic Surgery, 2024)
Abstract Background Tracheobronchial injuries caused by blunt chest trauma are rare in children, and such injuries usually involve multiple organs. Most cases involve respiratory failure on the way to the hospital, and the mortality rate is high. Herein, we describe the case of a 5-year-old patient who fell from an electric vehicle, causing complete rupture of the bilateral main bronchus. Case presentation We treated a 5-year-old patient with complete bilateral main bronchus rupture. Chest computed tomography (CT) failed to detect bronchial rupture. Continuous closed thoracic drainage resulted in a large amount of bubble overflow. Tracheal rupture was suspected. Fibreoptic bronchoscopy revealed complete rupture of the right main bronchus and rupture of the left main bronchus. Emergency tracheoplasty was performed under cardiopulmonary bypass (CPB). During the operation, we found that the bilateral main bronchi were completely ruptured. Postoperative recovery was smooth. The traditional surgical method for treating these injuries is lateral thoracotomy. However, a median sternotomy provides a better opportunity for selective repair. Extracorporeal circulation-assisted surgery is required for patients with unstable breathing. Conclusion Complete fractures of the bilateral main bronchi are rare. Bronchial rupture should be suspected in the presence of expansion defect-dropped lungs and massive air leakage despite tube thoracostomy in haemopneumothorax developing after thoracic trauma. Extracorporeal circulation-assisted tracheoplasty is a relatively safe option for children whose respiratory system is difficult to maintain, thus ensuring oxygenation ventilation and a clear surgical field.